Climate Change and Vulnerability in Local Areas: Attitudes to Evolving Risks and Adaptation in Two Pyrenean Valleys - Christine Bouisset; Sylvie Clarimont; Isabelle Degrémont (Revue de Géographie Alpine)
Drawing on our findings in the Western Pyrenees, this article aims to bring a better understanding of attitudes among local players, mainly elected representatives but also residents, to change - especially climate change - and how these changes are likely to affect the vulnerability to risks of mountain areas in the shorter or longer term. Vulnerability depends not only on the nature, scale and intensity of the changes to which a territorial system is exposed, but also on its sensitivity and capacity for adaptation (IPCC, 2001 and 2014). It is also exacerbated by scientific uncertainties as to how the climate is evolving and over the risks that arise, which are particularly evident at the local level. We show that difficulties in grasping current and future changes add to the vulnerability of the areas investigated.